Math, asked by ashiverma001, 5 months ago

If (–3)^(m+1) × (-3)^5 = (-3)^7, then the value of m is:

5

7

1

3​

Answers

Answered by parameshparamesh
5

Question:

 { (- 3)}^{m + 1}  \times  { (- 3)}^{7}  = {( - 3)}^{7}

Find the value of m…

Answer:

 {( - 3)}^{m + 1}  \times  { (- 3)}^{7}  =  {( - 3)}^{7}

w.k.t. \\  {a}^{m}  \times  {a}^{n}  =  {a}^{m + n}

 {( - 3)}^{m + 1 + 7}  =  {( - 3)}^{7}

 {( - 3)}^{m + 8}  =  {( - 3)}^{7}

Balancing the powers

m + 8 = 7

m = 7 - 8

m = ( - 1)

Similar questions